Strategi Komunikasi Dosen Dan Mahasiswa Dalam Meningkatkan Kualitas Pembelajaran Daring Selama Pandemik Covid-19 - Nawiroh Vera (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
The purpose of this study was to analyze the communication strategies of lecturers and students in overcoming obstacles and boredom in online learning in the Communication Theory course. The research approach is qualitative with the case study method, the informant is a lecturer and 45 students. The results showed that during online lectures students tended to feel bored and get a culture shock in the learning process. To overcome this, the lecturer implements two-way communication, giving students the opportunity to respond either in the form of questions, discussions, and comments on what is conveyed by the lecturer. Lecturers position themselves as motivators by promoting polite communication, being able to be good listeners, and being the first to take the initiative, so that students dare to express opinions actively. it also needs to be the attention of lecturers and students to be active, creative and innovative. The right communication strategy is proven to be able to eliminate boredom in online lectures which in turn can improve the quality of learning.